Acrodermatitis Chronica Atrophicans in a Patient with Pulmonary Sarcoidosis: Case Report and Literature Review - Simona Roxana Georgescu; Alexandra Florentina Dobrescu; Ela Ghiță; Iulia Maria Teodora Leulescu; Mircea Tampa (Journal of Mind and Medical Sciences, 2025)
Introduction: Acrodermatitis chronica atrophicans (ACA) is a late-stage cutaneous manifestation of Lyme borreliosis, primarily caused by Borrelia afzelii. It mainly affects the distal limbs and leads to progressive skin atrophy. Unlike other Lyme disease rashes, ACA does not resolve on its own and can worsen into severe atrophy and fibrosis if left untreated. Diagnosing ACA can be difficult due to its delayed onset and subtle symptoms, requiring clinical evaluation, multiple blood tests, and skin biopsy. Case presentation: We present the case of a 48-year-old female with a history of pulmonary sarcoidosis who presented to our clinic with multiple erythemato-violaceous patches over her left lower leg and was initially misdiagnosed with venous insufficiency. Histopathological and serological analyses confirmed ACA in its inflammatory phase. The patient responded well to a 30-day course of doxycycline, achieving complete resolution. This report underscores the importance of considering ACA in differential diagnoses and provides a comprehensive review of its pathogenesis, clinical progression, histopathological features, and epidemiology. Conclusions: This case emphasizes the need to consider acrodermatitis chronica atrophicans (ACA) in the differential diagnosis of chronic skin lesions. Clinicians should maintain a high index of suspicion for ACA, particularly in atypical presentations. When the diagnosis is uncertain but clinical suspicion persists, skin biopsy is recommended for histopathologic confirmation. Early diagnosis and appropriate antibiotic therapy are essential to prevent disease progression and irreversible cutaneous atrophy. Accurate diagnosis and effective management require a multidisciplinary approach, involving close collaboration between dermatologists, pathologists, and infectious disease specialists.